Numerical Evaluation of Thermal Striping in MLNG Tiga Regenerative Piping - ZULKIFLI, MUHAMMAD AFIQ IKHWAN (IRC, 2020)
Temperature fluctuations or known as thermal striping able to develop cyclic thermal stresses resulting in thermal fatigue. This can lead to unexpected failure of pipe material. New design of the T-junction has been made due to the raising concern regarding the current MLNG Tiga regenerative piping mixing tee design, which may degrade further as operations continue. However, there is no guarantee at the moment that the new colliding T-Junction design will improve in terms of magnitude and frequency of temperature fluctuations and temperature distribution along the mixing tee. This paper will discuss the behaviour of thermal striping at two different T-junction configuration which is the intersecting T-junction and colliding T-junction in MLNG Tiga regenerative piping.